Perlakuan Akuntansi Aset Tetap Pada Dinas Pengelolaan Keuangan Dan Aset Daerah Kota Semarang - (Jurusan Akuntansi Politeknik Negeri Semarang), Mulyati Setyaningsih, Adilistiono (Teknis, 2015)
The Objective of this study to find out accounting treatment of fixed assets based on the Indonesian Government Regulation Number 71 of 2010 on Government Accounting Standards and regional assets management. Writing method is used are the descriptive method and exposition method. Description method is used to describe the general overview, organizational structure and exposition method is used to explain about fixed assets treatment and regional assets management. Treatment of fixed assets in the Semarang already suitable with Government Regulation and decrement increment regional assets management also already suitable Government Regulation Number 27 of 2014 on Assets State/Regional Owned Management.Keywords: Accounting Treatment of Fixed Assets, Regional Assets Management, Government Regulation Number 71 of 2010, Government Regulation Number 27 of 2014.